Self-Employment and Migration - Giambra, Samuele; McKenzie, David (World Bank, Washington, DC, 2019)
There is a widespread policy view that a lack of job opportunities at home is a key reason for migration, accompanied by suggestions of the need to spend more on creating these opportunities to reduce migration. Self-employment is widespread in poor countries, and faced with a lack of existing jobs, providing more opportunities for people to start businesses is a key policy option. But empirical evidence to support this idea is slight, and economic theory offers several reasons why the self-employed may be more likely to migrate. This paper puts together panel surveys from eight countries to descriptively examine the relationship between migration and self-employment, finding that the self-employed are indeed less likely to migrate than wage workers or the unemployed. The paper then analyzes seven randomized experiments that increased self-employment, and finds that their causal impacts on migration are negative on average, but often small in magnitude.